Enzymatically Transformable Polymersome‐Based Nanotherapeutics to Eliminate Minimal Relapsable Cancer. Issue 49 (7th October 2021) - Li, Junjie; Ge, Zhishen; Toh, Kazuko; Liu, Xueying; Dirisala, Anjaneyulu; Ke, Wendong; Wen, Panyue; Zhou, Hang; Wang, Zheng; Xiao, Shiyan; Van Guyse, Joachim F. R.; Tockary, Theofilus A.; et al.
Abstract: Prevention of metastatic and local‐regional recurrence of cancer after surgery remains difficult. Targeting postsurgical premetastatic niche and microresiduals presents an excellent prospective opportunity but is often challenged by poor therapeutic delivery into minimal residual tumors. Here, an enzymatically transformable polymer‐based nanotherapeutic approach is presented that exploits matrix metalloproteinase (MMP) overactivation in tumor‐associated tissues to guide the codelivery of colchicine (microtubule‐disrupting and anti‐inflammatory agent) and marimastat (MMP inhibitor). The dePEGylation of polymersomes catalyzed by MMPs not only exposes the guanidine moiety to improve tissue/cell‐targeting/retention to increase bioavailability, but also differentially releases marimastat and colchicine to engage their extracellular (MMPs) and intracellular (microtubules) targets of action, respectively. In primary tumors/overt metastases, the vasculature‐specific targeting of nanotherapeutics can function synchronously with the enhanced permeability and retention effect to deter malignant progression of metastatic breast cancer. After the surgical removal of large primary tumors, nanotherapeutic agents are localized in the premetastatic niche and at the site of the postsurgical wound, disrupting the premetastatic microenvironment and eliminating microresiduals, which radically reduces metastatic and local‐regional recurrence. The findings suggest that nanotherapeutics can safely widen the therapeutic window to resuscitate colchicine and MMP inhibitors for other inflammatory disorders. Abstract : An enzymatically transformable nanotherapeutics is presented to improve the targeted delivery of old drugs—MMP inhibitor and colchicine—into minimal relapsable cancer. This distinct combination therapy not only ensures direct killing of residual cancer cells but also disrupts the premetastatic microenvironment to prevent distant seeding/outgrowth, which radically reduces metastatic and local‐regional recurrence after surgery.